X-ray production simulation of an electron beam recycled through a betatron's internal target - Kaplin V. V. Valeriy Viktorovich; Lombardo L. W.; Mikhalchuk A. A. Aleksandr Alexandrovich; Piestrup M. A.; Uglov S. R. Sergey Romanovich (1998, 1998)
Title screen